Cooperativity between the 3' untranslated region microRNA binding sites is critical for the virulence of eastern equine encephalitis virus. - Derek W Trobaugh; Chengqun Sun; Nishank Bhalla; Christina L Gardner; Matthew D Dunn; William B Klimstra (PLoS Pathogens)
Eastern equine encephalitis virus (EEEV), a mosquito-borne RNA virus, is one of the most acutely virulent viruses endemic to the Americas, causing between 30% and 70% mortality in symptomatic human cases. A major factor in the virulence of EEEV is the presence of four binding sites for the hematopoietic cell-specific microRNA, miR-142-3p, in the 3' untranslated region (3' UTR) of the virus. Three of the sites are "canonical" with all 7 seed sequence residues complimentary to miR-142-3p while one is "non-canonical" and has a seed sequence mismatch. Interaction of the EEEV genome with miR-142-3p limits virus replication in myeloid cells and suppresses the systemic innate immune response, greatly exacerbating EEEV neurovirulence. The presence of the miRNA binding sequences is also required for efficient EEEV replication in mosquitoes and, therefore, essential for transmission of the virus. In the current studies, we have examined the role of each binding site by point mutagenesis of the seed sequences in all combinations of sites followed by infection of mammalian myeloid cells, mosquito cells and mice. The resulting data indicate that both canonical and non-canonical sites contribute to cell infection and animal virulence, however, surprisingly, all sites are rapidly deleted from EEEV genomes shortly after infection of myeloid cells or mice. Finally, we show that the virulence of a related encephalitis virus, western equine encephalitis virus, is also dependent upon miR-142-3p binding sites.